Multi-objective Process Optimization Analysis of Cold Rotary Forging for Hypoid Gear - Dang Yugong; Gao Zhenshan; Lu Yangben; Deng Xiaozhong (Jixie chuandong)
According to the requirement of anti-fatigue manufacture and characteristics of hypoid gear tooth profile,a special cold rotary forging scheme is put forward. By using the orthogonal numerical simulation,the influence law of process parameters on experiment index,the forming force and maximum springback of tooth surface,are studied through numerical simulation,and the optimal combination of process parameters within a certain range is got,and the regression analysis and correlation test of simulation results are performed.This research result can provide certain reference value for process design in actual production.